2013
DOI: 10.1074/jbc.m113.457648
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Myoblast Proliferation and Fibroblast Growth Factor Receptor 1 Promoter Activity by KLF10 Protein

Abstract: Background: FGFR1 gene expression regulates myoblast proliferation and differentiation, and its expression is controlled by Krüppel-like transcription factors. Results: KLF10 interacts with the FGFR1 promoter, repressing its activity and cell proliferation. Conclusion: KLF10 represses FGFR1 promoter activity and thereby myoblast proliferation. Significance: A model of transcriptional control of chicken FGFR1 gene regulation during myogenesis is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
(60 reference statements)
1
23
0
Order By: Relevance
“…9). Additionally, some genes involved in the smooth muscle maturation and skeletal myogenesis, as reported in previous studies (31)(32)(33)(34)(35)(36), were also found to be differentially expressed in CK14-Cre;Shh fl/fl mutant mice ( Fig. 9).…”
Section: Discussionsupporting
confidence: 78%
“…9). Additionally, some genes involved in the smooth muscle maturation and skeletal myogenesis, as reported in previous studies (31)(32)(33)(34)(35)(36), were also found to be differentially expressed in CK14-Cre;Shh fl/fl mutant mice ( Fig. 9).…”
Section: Discussionsupporting
confidence: 78%
“…It has been found that the KLF10 protein could repress the proliferation of myoblasts and the activity of fibroblast growth factor receptor 1 promoter. 19 KLF3 regulates the expression of muscle-specific genes through binding to their promoters. 20 Many studies have shown that KLF6 can regulate various physiological and pathological processes, such as homeostasis, 21 lipid metabolism, adipocyte proliferation, 22 and proliferation and apoptosis of bovine muscle cells 23 and lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…This effect on FGFR1 gene expression generally correlates with the altered proliferation and differentiation of C 2 C 12 cells overexpressing KLF10. 29,30 KLF10 also mediates TGF-b signaling through transcriptional regulation of genes encoding SMAD isoforms. KLF10 represses SMAD7 gene expression, but conversely activates SMAD2 gene expression.…”
mentioning
confidence: 99%